2011
DOI: 10.1167/iovs.10-5685
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Oculomotor Characteristics of Albinism Compared toFRMD7Associated Infantile Nystagmus

Abstract: Differences in nystagmus characteristics associated with albinism and those associated with FRMD7 mutations leading to IIN are described for the first-time. These findings may provide useful information in the future elucidation of mechanisms underlying the nystagmus associated with albinism and idiopathic infantile nystagmus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…Because nystagmography is not routinely available in pediatric ophthalmology offices, and because the utility of such recordings for diagnosis in a large clinical sample have not been studied, this would be a fertile area for further research. A study comparing the nystagmus of albinism patients and FRMD7-related patients found that while there were group differences the differences between individuals were not diagnostic (25). In our study population we found essentially the same phenomenon ( Figure 8).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Because nystagmography is not routinely available in pediatric ophthalmology offices, and because the utility of such recordings for diagnosis in a large clinical sample have not been studied, this would be a fertile area for further research. A study comparing the nystagmus of albinism patients and FRMD7-related patients found that while there were group differences the differences between individuals were not diagnostic (25). In our study population we found essentially the same phenomenon ( Figure 8).…”
Section: Discussionsupporting
confidence: 77%
“…This type of nystagmus appears very similar to the nystagmus seen in albinism, however on nystagmography there are subtle differences (25). Patients with FRMD7 motor nystagmus have no iris transillumination defects and a fovea is present on OCT, although at least one report states the foveas may be thinner than normal (26).…”
Section: Motor Nystagmus (Idiopathic Infantile Nystagmus)-examplar Camentioning
confidence: 75%
“…26 Thus, it is possible that multiple gaze control centres are affected in patients with PAX6 mutations, resulting in the nystagmus on various planes as compared with other patients with infantile nystagmus, who invariably have horizontal nystagmus. 27 Furthermore, the postnatal development of the visual system may be affected by afferent …”
Section: Discussionmentioning
confidence: 99%
“…Nystagmus characteristics are usually captured in the following parameters: amplitude, frequency, intensity (i.e., amplitude × frequency), foveation characteristics and waveform types (Kumar et al, 2011). Longer foveation periods, i.e., the time during which a stable foveal image is present, are related to better visual acuity (Dell'osso and Daroff, 1975; Abadi and Worfolk, 1989; Bedell and Currie, 1993).…”
Section: Introductionmentioning
confidence: 99%